2000
DOI: 10.1074/jbc.m004045200
|View full text |Cite
|
Sign up to set email alerts
|

Induction of IκBα Expression as a Mechanism Contributing to the Anti-inflammatory Activities of Peroxisome Proliferator-activated Receptor-α Activators

Abstract: Chronic inflammation is a hallmark of degenerative diseases such as atherosclerosis. Peroxisome proliferator-activated receptors (PPARs) are transcription factors belonging to the nuclear receptor superfamily, which are expressed in the cells of the atherosclerosic lesion. PPAR␣ ligands have been reported to exert antiinflammatory activities in different cell types by antagonizing the transcriptional activity of NF-B. In the present study, the influence of PPAR␣ activators on the NF-B signaling pathway was inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
268
1
7

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 434 publications
(291 citation statements)
references
References 46 publications
15
268
1
7
Order By: Relevance
“…Alternatively, inhibitory effects might occur through competitive binding of transcriptional coactivators by PPAR or by PPAR -induced transcription factors. Moreover, longer exposure to fibrates was found to induce I B mRNA and protein expression in primary smooth muscle cells and hepatocytes (Delerive et al, 2000). Future study should investigate these inhibitory effects of fibrates via PPAR on chenodeoxycholic acid-induced RANTES expression in human hepatocytes.…”
Section: Discussionmentioning
confidence: 91%
“…Alternatively, inhibitory effects might occur through competitive binding of transcriptional coactivators by PPAR or by PPAR -induced transcription factors. Moreover, longer exposure to fibrates was found to induce I B mRNA and protein expression in primary smooth muscle cells and hepatocytes (Delerive et al, 2000). Future study should investigate these inhibitory effects of fibrates via PPAR on chenodeoxycholic acid-induced RANTES expression in human hepatocytes.…”
Section: Discussionmentioning
confidence: 91%
“…Studies by Daynes and colleagues (31) have shown that in vivo administration of PPAR␣ ligands to aged mice diminishes their augmented NF-B levels. Fibrates may also inhibit NF-B DNA binding activity by augmenting the expression of I B␣ (32). In addition, in vivo administration of WY14,643 to aged mice corrects the dysregulation of IFN-␥ and splenic inducible NO synthase, as well as the elevated splenocyte levels of IL-6 and IL-12 (31, 33).…”
Section: Discussionmentioning
confidence: 99%
“…33 PPARa may also increase the level of nuclear IkBa, leading to reduction in NF-kB DNAbinding activity. 34 In contrast to the abundant information on the suppressive effect of PPARa on NF-kB, little is known about anti-inflammatory effects of other PPARs. In vascular smooth muscle cells and endothelial cells, previous reports showed that, in contrast to PPARa agonists, PPARg agonists did not influence cytokine-induced activation of NF-kB.…”
Section: Selective Loss Of Adipocytes By Tnf-a M Tamai Et Almentioning
confidence: 99%